Simulation and experimental characterization of gyromagnetic nonlinear transmission lines for prospective aerospace applications - Fernanda Sayuri Yamasaki (2017)
A great interest has been devoted to the study of nonlinear transmission lines (NLTLs) for radiofrequency (RF) generation since they have been used with great success in RF generation by producing a train of oscillatory waves along the line and at its output. There are two configurations of NLTLs. The first one is a dispersive line consisting of LC sections with nonlinear components, and the second one is a continuous ferrite loaded non-dispersive line generally biased by an axial magnetic field, known as gyromagnetic line. In this thesis, the focus of the study is on the second one, since gyromagnetic lines can operate in a broader frequency range (0.4 up to 2.0 GHz) with higher conversion efficiency (20.0 %) when compared to lumped NLTLs limited up to 300.0 MHz with less than 10.0 % of efficiency, because of their dielectric losses and stray impedances on line structure. Different models have been used along the years by several authors with different approaches to study the gyromagnetic phenomenon by means of numerical simulations based on analytical models to predict the precession movement of the electron magnetic dipole of the ferrimagnetic material. Thus, the goal of this thesis is to analyze the gyromagnetic NLTL behavior through the effects on the line operation by changing its parameters. The novelty herein is to use Spice simulations based on LC lumped line models to study continuous gyromagnetic NLTLs in addition to numerical simulations usually employed, focusing on the pulse rise time compression and RF generation caused by magnetic dipole precession. Different models are studied by comparing Spice simulations with corresponding results from numerical simulations and experiments found in the literature. Finally, an experimental set-up is described for a 20-cm gyromagnetic line loaded with NiZn ferrite beads to validate with data the proposed method based on Spice simulations. Finally, it is expected that such Spice techniques can be used in the design of these continuous lines for RF applications in space and mobile defense platforms of compact size.